2020
DOI: 10.3389/fphys.2020.575485
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Carbohydrate Metabolism by Trehalose-6-Phosphate Synthase 3 in the Brown Planthopper, Nilaparvata lugens

Abstract: Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) is one of the pests that harm rice. In this paper, a new trehalose-6-phosphate synthase gene, TPS3, was identified by transcriptome sequencing and gene cloning. To explore its role in the energy metabolism of N. lugens we examined the carbohydrate contents at different stages of development, the tissue expression of TPS, and some physiological and biochemical indicators by injecting dsTPS3 and dsTPSs (a proportional mixture of dsTPS1, dsTPS2, and dsTPS3). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…As in mammals, circulating sugar levels in insects are mainly regulated by the action of two peptide hormone families, ILPs and AKHs ( Toprak, 2020 ). The control of trehalose metabolism by ILPs, including circulating trehalose levels, as well as their participation in regulating the expression of trehalases and TPS, has been reported in several species ( Bounias et al, 1993 ; Satake et al, 1997 ; Iwami, 2000 ; Wu and Brown, 2006 ; Broughton et al, 2008 ; Wang et al, 2020 ). However, until now, the link between insulin signaling and TRET has been scarcely studied, even though in vertebrates glucose transporter 4 (GLUT4) is translocated to the plasma membrane in response to insulin signals ( Bryant and Gould, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As in mammals, circulating sugar levels in insects are mainly regulated by the action of two peptide hormone families, ILPs and AKHs ( Toprak, 2020 ). The control of trehalose metabolism by ILPs, including circulating trehalose levels, as well as their participation in regulating the expression of trehalases and TPS, has been reported in several species ( Bounias et al, 1993 ; Satake et al, 1997 ; Iwami, 2000 ; Wu and Brown, 2006 ; Broughton et al, 2008 ; Wang et al, 2020 ). However, until now, the link between insulin signaling and TRET has been scarcely studied, even though in vertebrates glucose transporter 4 (GLUT4) is translocated to the plasma membrane in response to insulin signals ( Bryant and Gould, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molting and metamorphosis are important for insects ( Ishimaru et al, 2016 ). The energy required for metamorphosis is extracted from the energy stored during larval rearing ( Merkey et al, 2011 ; Wang et al, 2020 ). Surprisingly, in Samia cynthia ( Hetz, 2007 ), Zophobas rugipes ( Kaiser et al, 2010 ), and Apis mellifera ( Schmolz et al, 2005 ), low energy consumption during metamorphosis was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of trehalose in insects is carried out by TPS in the fat body and is regulated by hormones. The author's research team has cloned three TPS genes from the rice pest brown planthopper (Tang et al, 2019; S. S. Wang et al, 2020; M. M. Yang et al, 2017). Studies have shown that the trehalose metabolism of N. lugens would be affected when the expression level of three TPS genes was inhibited either alone or in combination (Figure 1) (S. S. Wang et al, 2020; M. M. Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The author's research team has cloned three TPS genes from the rice pest brown planthopper (Tang et al, 2019; S. S. Wang et al, 2020; M. M. Yang et al, 2017). Studies have shown that the trehalose metabolism of N. lugens would be affected when the expression level of three TPS genes was inhibited either alone or in combination (Figure 1) (S. S. Wang et al, 2020; M. M. Yang et al, 2017). However, in N. lugens , the expression level of TRE1‐1 decreased and trehalose content increased after injection of ds TPS2 (M. M. Yang et al, 2017); the expression level of TRE1‐1 increased and trehalose content decreased after injection of ds TPS3 (Figure 1) (S. S. Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%